Strategi Pengembangan Bisnis Pariwisata Dan Ekonomi Kreatif Berbasis Website Vacancy (Vacation Fancy) - Mohammad Vavian Baharudinsyah; Yanda Bara Kusuma (Sekolah Tinggi Pastoral Kateketik Santo Fransiskus Assisi, 2023)
Tourism and the creative economy are sectors that are promising and have a great opportunity to support the economy, so they need to be a top priority. However, the reality is that the development of creative economy-based tourism potential has faced many problems, such as inadequate human resources and even insufficient promotion, so that many domestic and foreign tourists are not aware of the existence of unique and attractive destinations in East Java. Preliminary case studies have been carried out involving 25 communities to analyze the problems that occur in tourism and the creative economy in East Java Province. Based on the results of the study, the development of e-tourism-based promotions is crucial amidst the rise of technological developments. The Vacancy website is an e-tourism-based promotion that can accommodate the needs of tourism and the creative economy in East Java. In addition, promotion is also a major factor in supporting the introduction of creative economy-based tourism. This Vacancy website is able to provide accurate information related to tourism and the creative economy and facilitate accessibility to destinations with the support of various existing features such as recommendations, accommodation, regional culture, and other complete features.